2011
DOI: 10.1073/pnas.1117011108
|View full text |Cite
|
Sign up to set email alerts
|

Effects of brefeldin A-inhibited guanine nucleotide-exchange (BIG) 1 and KANK1 proteins on cell polarity and directed migration during wound healing

Abstract: Brefeldin A-inhibited guanine nucleotide-exchange protein (BIG) 1 activates class I ADP ribosylation factors (ARFs) by accelerating the replacement of bound GDP with GTP to initiate recruitment of coat proteins for membrane vesicle formation. Among proteins that interact with BIG1, kinesin family member 21A (KIF21A), a plusend-directed motor protein, moves cargo away from the microtubule-organizing center (MTOC) on microtubules. Because KANK1, a protein containing N-terminal KN, C-terminal ankyrin-repeat, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
43
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(48 citation statements)
references
References 54 publications
3
43
1
Order By: Relevance
“…In addition to roles for BIG1 in control of cell polarity during directed migration (31), and appropriate integrin β1 N-glycosylation (30) as well as for BIG2 in its intracellular trafficking (28), we show here that both BIG1 and BIG2, via multiple, different actions, contributed to PKA-catalyzed phosphorylation of β-catenin with resulting enhancement of cyclin D and c-myc transcription, whether or not initiated by Wnt signaling.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to roles for BIG1 in control of cell polarity during directed migration (31), and appropriate integrin β1 N-glycosylation (30) as well as for BIG2 in its intracellular trafficking (28), we show here that both BIG1 and BIG2, via multiple, different actions, contributed to PKA-catalyzed phosphorylation of β-catenin with resulting enhancement of cyclin D and c-myc transcription, whether or not initiated by Wnt signaling.…”
Section: Discussionmentioning
confidence: 99%
“…Microscopically, BIG1 was seen mainly at the trans-Golgi network (TGN), sometimes partially overlapping BIG2, which was associated also with recycling endosomes (24-26), e.g., in moving proteins and lipids among TGN, endosomes, and cell surface (24,(27)(28)(29). Although actions of BIG1 and BIG2 at the TGN were described as "redundant" (27), each protein clearly has specific roles in moving proteins and lipids that are not shared with the other (24,30,31). Overexpression in cultured cells of mutant BIG2 lacking Arf GEF activity markedly altered intracellular distributions of E-cadherin and β-catenin (32).…”
mentioning
confidence: 99%
“…Recently, we found that liprin-b1 interacts with KANK1 (van der Vaart et al, 2013), one of the four members of the KANK family of proteins, which were proposed to act as tumor suppressors and regulators of cell polarity and migration through Rho GTPase signaling (Gee et al, 2015;Kakinuma et al, 2008Li et al, 2011;Roy et al, 2009). KANK1 recruits the kinesin-4 KIF21A to CMSCs, which inhibits microtubule polymerization and prevents microtubule overgrowth at the cell edge van der Vaart et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…tion of mature integrin β1 (23), and directed migration during wound healing (24). In contrast, BIG2 was involved in recycling of internalized transferrin receptors (21) and integrin β1 (25) to the cell surface, and in regulation of tumor necrosis factor receptor release in exosome-like vesicles (26).…”
mentioning
confidence: 99%
“…PP1γ (29) and phosphodiesterase 3A (30) that, respectively, dephosphorylate PKA-modified BIG1 and BIG2 and terminate cAMP signals, have been identified in complexes with BIG1 and/or BIG2. Depletion of BIG1 or BIG2 was reported to decrease cell motility as well as actin-based membrane protrusions (24,25), although the mechanisms through which these proteins altered cytoskeleton dynamics remain unclear. Here, we provide evidence that NM IIA activity in HeLa cells, which is crucial for actin stress fiber formation, is also influenced by previously unrecognized interactions with the C termini of BIG1 and BIG2, independent of Arf GEF activity, in complexes that include PP1cδ, and MYPT1.…”
mentioning
confidence: 99%